The Determinants of Housing Prices: Evidence from Chinese Cities - Yang Wanli (SHS Web of Conferences, 2022)
With the rapid growth of China’s economy, the urbanization process is accelerating, and urban development is getting faster and faster. Housing prices have become a concern for more and more residents. This paper empirically studies the determinants of housing prices, including population, region, land factors, and government fiscal measures. Multiple linear regression models interpret the economic implications of empirical results by collecting unique data sets from multiple sources. The results show that government fiscal revenue, real estate investment, and land value positively correlate to housing prices. This article makes insightful comments on the above analysis, which is significant to the government, real estate developers, and residents. To a large extent, the government can take measures to adjust the housing price and solve the housing problem. Achieve the purpose of sustainable development.